Hydrobeep / Wan Shafiq Aqil … [et al.] - -, Wan Shafiq Aqil; -, Muhammad Fazlie Hakimie; -, Muhammad Amirul Haikal; -, Nurnafisah Najla; -, Aina Najihah; -, Siti Fatimah Azzahra; -, Syahiru Shafiai (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The issue of neglecting to hydrate is often looked past by certain individuals who are caught up with working which can make their body frail because of not drinking sufficient water for a person. With plastic water bottles possessing the top level of socially unsuitable single-use embellishments, reusable water bottles that are both gorgeous and practical feel like a need in this cutting-edge, hydration-fixated world. Hydrobeep is a stainless-steel water bottle, your goto eco-friendly reusable sidekick. A premium alternative for a water flask. It is vacuuminsulated and keeps cold drinks cold, hot drinks hot for hours. The opening is designed wide enough to have room for loading in ice. It is the unique combination of temperature, taste that allows Hydrobeep to deliver refreshment anytime, anywhere. It is to be made with durable prograde stainless steel that claims to not retain or transfer flavours. The material Hydrobeep is made out of provides durability against scuffing, weather and water. As it is easy to grip, sweatfree and durable, it is a necessity that it is convenient anywhere. The temperature control and visibility allow the chances of burning yourself with hot boiling water close to none. Introducing a new feature, the reasoning for its name, the bottle beeps as a precautionary warning for those who tend to forget to consume their water intake. It works as a reminder and will be effective for those who are too preoccupied with their task that they neglect their dehydrated body. There is also a USB port to charge the bottle which lasts up to 48 hours on full capacity. Perfect for those who want a chameleon of a bottle, something that adapts to almost any situation.